The Concept of Heteronomy in the Ethics of Lévinas and Caputo - Mickiewicz, Adriana Joanna (Sensus Historiae, 2023)
The aim of this article is to compare and contrast the conception of heteronomy in the works of Emmanuel Lévinas and John D. Caputo. I am going to examine the historical connections between those authors. The notion of heteronomy will be analyzed in the framework of the idea of autonomy that has gained its most developed form in the philosophy of the Enlightenment. Critical analysis of the use of the philosophy of Lévinas and Caputo will enable me to raise the question about the limitations of the heteronymous approach in ethics. According to my thesis, it is not possible to create a purely heteronomous concept; yet, neither should pure autonomous ethics be pursued. These two attitudes must coexist with each other for the establishment of the possibility of a real moral response to the Other.